Lembar Fakta Trafficking Untuk Anak Yang Dilacurkan di Indonesia dan Penegakan Hukumnya - Handayani, I Gusti Ayu Ketut Rachmi; Zamroni, Mohammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
Human trafficking is one of activities that constitute serious violence against human rights, particularly the rights of women and children trafficked. In fact, trafficking has become a universal phenomenon and is considered the enemy of all countries in the world. In Indonesia, women and children are trafficked from one country to another and within the country itself. They are trafficked for domestic work, waiters, entertainers, booked brides, beggars or prostitution. Law enforcement in both national and international levels has been conducted. The laws, nevertheless, cannot effectively overcome the problem of trafficking in women and children